Application of new forms of fertilizers to improve productivity and grain quality of white lupine - G. L. Yagovenko; Т. V. Yagovenko; Т. N. Slesareva; N. M. Zaitseva; N. V. Misnikova (Зерновое хозяйство России)
Substantiation and development of technology elements for obtaining a sustainable productivity of lupine grain is an important and urgent task for expanding the area under this grain crop. There have been considered the study results of the effect of fertilizers ‘Aquamix ST’, ‘Metaborat Kaliya’, ‘Tiaton’ on productivity and grain quality of white lupine. The study was carried out at the All-Russian Research Institute of Lupine – a branch of the FWRC FPA, in the soil and climatic conditions of the southwestern part of the Non-Chernozem zone in 2018-2019. The purpose of the current study was to estimate the efficiency of these innovative micro- and macrofertilizers and the methods of their application on a number of indicators that improve productivity and grain quality of white lupine. The application of fertilizers ‘Aquamix ST’ and ‘Metaborat Kaliya’ contributed to an increase of white lupine grain productivity on 37.5 and 35.4%. There has been determined protein increase from 5.0 to 5.8% in grain of the white lupine variety ‘Piligrim’ in all application variants of ‘Aquamix ST’. The use of ‘Aquamix ST’ and ‘Metaborat Kaliya’ in the vegetation period of plants reduced alkaloid content of lupine grain on 24.7-34.6%. Application of ‘Aquamix ST’ and ‘Metaborat Kaliya’ in white lupine budding stage increased carotene content in grain on 34.3 and 25.0%, respectively. The analysis of the data showed that the variant including pre-seeding treatment with ‘Aquamix ST’ and subsequent treatment in the budding stage of plants was characterized by the maximum amount of lysine and carotene. There was noted that the application of micro- and macrofertilizers resulted in an increase in feed units and digestible protein. Application of ‘Aquamix ST’, including pre-seeding treatment and two treatments in the vegetation period of plants provided the largest yield of digestible protein (1.26 t/ha), 6.0 t/h of feed units, and 54.8 GJ/ha of exchangeable energy. ‘Metaborat Kaliya’, used in the treatment of plants in their budding phase, showed almost the same results. The options that combined high productivity with high grain quality were more valuable according their feed value.